Open surgical revision of radial nerve after humeral fracture in polytrauma - Bernobi, Sergio; De Fabrizio, Giovanni; Vuga, Matjaz; Valentini, Roberto (Acta Biomedica Atenei Parmensis, 2014)
Aim of the study: The injury of the radial nerve is not uncommon in humeral shaft fractures. These lesions may be of different types and levels and their treatment changes depending on traumatic characteristic. The authors present a case report of a patient affected by a closed shaft humeral fracture, consequence of an high energy trauma, associated with motor palsy of the radial nerve in which an open surgical revision was performed. The nerve appeared medially displaced and entrapped within the fracture fragments and the fibrous tissue around the lesion and showed signs of posttraumatic suffering without disruption. The nerve was repositioned in its anatomical site after neurolysis and intramedullary nailing of the humeral fracture. The fracture healed after 4 months with full recovery of motor function of the radial nerve.We believe that, in shaft fractures of the humerus with radial nerve deficits, it is imperative to perform surgical exploration of the conditions of the radial nerve itself, in order to obtain a recovery of its functionality.